2019
DOI: 10.1016/j.ejvs.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Lead Aprons: The Emperor's New Clothes in the Angiography Suite?

Abstract: The aim of this study was to test the performance and labelling of garments that are in contemporary use for radiation protection. A significant proportion of garments failed to comply with international labelling standards and did not provide the protection claimed by manufacturers. In addition, garments labelled at the same lead equivalence performed vastly differently in attenuation of scatter. These findings were demonstrated in the real world setting, by testing garments that are in current use across mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
(14 reference statements)
0
9
0
3
Order By: Relevance
“…Leadfree aprons might weigh up to 25% less (6). However, the measured lead equivalent of leadfree aprons might be lower than expected according to some studies (2,(7)(8)(9), fact disproved by other studies (6,10).…”
Section: Introductionmentioning
confidence: 82%
“…Leadfree aprons might weigh up to 25% less (6). However, the measured lead equivalent of leadfree aprons might be lower than expected according to some studies (2,(7)(8)(9), fact disproved by other studies (6,10).…”
Section: Introductionmentioning
confidence: 82%
“…Jak wynika z informacji dystrybutorów, ulegają one ponadto recyklingowi lub przynajmniej są bezpieczniejsze w utylizacji. Jako materiał tłumiący wykorzystuje się w nich głównie związki bizmutu, berylu [9], wolframu, antymonu, tytanu, magnezu lub mieszaniny tych pierwiastków [10]. Stosowane pierwiastki cechują się lepszą niż ołów efektywnością w pochłanianiu fotonów promieniowania RTG w zakresie 40-88 keV.…”
Section: Nowe-stare Sposoby -Stosowanie Osłonunclassified
“…Lu i wsp. [9] wykazali jednak, że fartuchy bezołowiowe mogą pochłaniać promieniowanie w stopniu mniejszym niż podany przez producenta ekwiwalent grubości ołowiu. Badacze stwierdzili, że 47% przetestowanych części przednich 15 fartuchów bezołowiowych i 90% ich części tylnych cechowało się zawyżonym ekwiwalentem ołowiu, tzn.…”
Section: Nowe-stare Sposoby -Stosowanie Osłonunclassified
See 1 more Smart Citation
“…Manufacturers often provide attenuation properties at a single beam energy (which is not particularly representative of vascular surgeons' daily practice), whereas it is well known that this varies significantly over the photon energy spectrum, especially with lightweight aprons. 4 In the study by Lu et al in this issue, 5 the authors demonstrated that in a random selection of "good shape" radiation protection garments found in the operating room, the Xray attenuation properties of the front panel were lower than expected in half the cases. Moreover, when garments had a back panel, attenuation was below the value stated by the manufacturers in 90% of cases.…”
mentioning
confidence: 96%